2021
DOI: 10.3126/mjmms.v1i1.42942
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Practice Regarding Prevention of COVID-19 among Community People During and After Lockdown

Abstract: INTRODUCTION: Due to erratic growth of COVID-19 infection across the globe, the mortality and morbidity due to COVID-19 is rapidly changing across the world. An assessment of the perception and practices of community members is important to reduce the risk for COVID-19 infection. Therefore, this study aims to assess the perception and practice regarding prevention of COVID-19 infection among community people before and after lockdown. MATERIALS AND METHODS: A cross-sectional study was conducted among com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The result was in line with the study conducted in Janakpur, Nepal which revealed that though the perception of COVID-19 was not so different, the preventive behaviors were reduced in post-lockdown compared to the behaviors during the lockdown. The less precautionary behavior was especially observed among those following unofficial sources of information after the lockdown compared to those following official government sites [79,80]. During a humanitarian crisis, such as a pandemic, the spread of rumors, and misleading information through social media and various other communication mediums, especially unofficial sources, can further impact the KAP level of community people, which leads to an increase in morbidity and mortality [81].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…The result was in line with the study conducted in Janakpur, Nepal which revealed that though the perception of COVID-19 was not so different, the preventive behaviors were reduced in post-lockdown compared to the behaviors during the lockdown. The less precautionary behavior was especially observed among those following unofficial sources of information after the lockdown compared to those following official government sites [79,80]. During a humanitarian crisis, such as a pandemic, the spread of rumors, and misleading information through social media and various other communication mediums, especially unofficial sources, can further impact the KAP level of community people, which leads to an increase in morbidity and mortality [81].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…The result was in line with the study conducted in Janakpur, Nepal which revealed that though the perception on COVID-19 was not so different, the preventive behaviors were reduced in post-lockdown compared to the behaviors during the lockdown. The less precautionary behavior was especially observed among those following unofficial sources of information after lockdown compared to those following official government sites (43). During a humanitarian crisis, such as a pandemic, the spread of rumors, and misleading information through social media and various other communication mediums especially unofficial sources can further impact the KAP level of community people which led to an increase in morbidity and mortality (44).…”
Section: Discussionmentioning
confidence: 99%